Parestesi pada fraktur kompleks zigomatikomaksilaris Paresthesia in zygomaticomaxillary complex fractures - Pedro Bernado; Prihartiningsih Prihartiningsih; Poerwati Soetji Rahajoe (DiscoverSys Inc., 2013)
Head trauma cases can involve os.zygoma and maxilla. Injury to the nerves is one of the complications that can beencountered as a result of the fracture fragments shift. This paper reported one case of n.infraorbitalis paresthesiafollowing zygomaticomaxillary complex fracture. A 30 years old man was referred to the Department of Oral Surgery,Dr.Sardjito Hospital with a history of traffic accident two weeks before admission. The patient complained of rightcheek area feels numbness, bite changed and there was a protrusion of bone under his right eye. Clinical examinationfound paresthesias of right n.infraorbitalis, left posterior open bite, and bone displace at right infraorbital rim. At theWater's x-ray and 3D CT scan visualized fractures involving the right maxillary and infraorbital rim. Open reductioninternal fixation (ORIF) zygomaticomaxillary complex fracture, with miniplate supported by arch bar as a device toachieve individually normal occlusions, was performed under general anesthesia. Postoperative follow up indicateparesthesia symptoms gradually decreased and totally recover within 5 months. Prognosis for this case was bonam. Itwas concluded that ORIF with miniplate, combined with mounting arch bar can support paresthesia correction due tothe displacing of fracture fragment zygomaticomaxillary complex.